Effects of alpha-methyldopa on the sympathetic nervous system activity in health participants - Greeff, O.B.W. (Oppel Bernhardt Wilhelm), 1948- (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.